Strategic implementation planning for integrated behavioral health services in pediatric primary care - Jennifer A Mautone; Courtney Benjamin Wolk; Zuleyha Cidav; Molly F Davis; Jami F Young (Implementation Research and Practice, 2021)
Background: Delivering physical and behavioral health services in a single setting is associated with improved quality of care and reduced health care costs. Few health systems implementing integrated care develop conceptual models and targeted measurement strategies a priori with an eye toward adoption, implementation, sustainment, and evaluation. This is a broad challenge in the field, which can make it difficult to disentangle why implementation is or is not successful. Method: This article discusses strategic implementation and evaluation planning for a pediatric integrated care program in a large health system. Our team developed a logic model, which defines resources and community characteristics, program components, evaluation activities, short-term activities, and intermediate and anticipated long-term patient-, clinician-, and practice-related outcomes. The model was designed based on research and stakeholder input to support strategic implementation and evaluation of the program. For each aspect of the logic model, a measurement battery was selected. Initial implementation data and intermediate outcomes from a pilot in five practices in a 30-practice pediatric primary care network are presented to illustrate how the logic model and evaluation plan have been used to guide the iterative process of program development. Results: A total of 4,619 office visits were completed during the 2 years of the pilot. Primary care clinicians were highly satisfied with the integrated primary care program and provided feedback on ways to further improve the program. Members of the primary care team and behavioral health providers rated the program as being relatively well integrated into the practices after the second year of the pilot. Conclusion: This logic model and evaluation plan provide a template for future projects integrating behavioral health services in non-specialty mental health settings, including pediatric primary care, and can be used broadly to provide structure to implementation and evaluation activities and promote replication of effective initiatives. Plain language abstract: Up to 1 in 5 youth have difficulties with mental health; however, the majority of these youth do not receive the care they need. Many youth seek support from their primary care clinicians. Pediatric primary care practices have increasingly integrated behavioral health clinicians into the care team to improve access to services and encourage high-quality team-based care. Definitions of “behavioral health integration” vary across disciplines and organizations, and little is known about how integrated behavioral health care is actually implemented in most pediatric settings. In addition, program evaluation activities have not included a thorough examination of long-term outcomes. This article provides detailed information on the implementation planning and evaluation activities for an integrated behavioral health program in pediatric primary care. This work has been guided by a logic model, an important implementation science tool to guide the development and evaluation of new programs and promote replication. The logic model and measurement plan we developed provides a guide for policy makers, researchers, and clinicians seeking to develop and evaluate similar programs in other systems and community settings. This work will enable greater adoption, implementation, and sustainment of integrated care models and increase access to high-quality care.